HEMATOLOGI KELINCI (Lepus sp.) SETELAH PERLAKUAN IMPLANTASI MATERIAL STAINLESS STEEL AISI 316L SELAMA 2,5 BULAN - Indriati, Martha Dian; Tana, Silvana; Mardiati, Siti Muflichatun (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2015)
Stainless Steel AISI 316L are one of the implant material used in the manufacture of artificial hip joint. Testing the effect of prior implantation needs to be done in animal models such as rabbits before applied in the human body. Future integration of the implant in the body of an animal model takes 4-6 weeks. This study aimed to analyze the body's physiological response to the implantation of an animal model of AISI 316L Stainless Steel for 2.5 months seen from the aspect of the number of erythrocytes, leukocytes and hemoglobin animal models as part of the basic data for further research in order to figure out orthopedic implants that can be used by the body. This study compares the P0: control rabbits and Ps: rabbits given the implants Stainless Steel AISI 316L. The parameters measured were the number of erythrocytes, leukocyte count and hemoglobin levels, feed intake and body weight were analyzed by Independent Sample T test with SPSS procedures at 95% significance level. The results showed red cell count, leukocyte count and hemoglobin levels did not differ significantly (p> 0.05) between the control treatment. It can be concluded that the use of stainless steel AISI 316L for 2.5 months had no effect on animal physiology and is a material that can be used by the body. Â Keywords: Rabbit, stainless steel AISI 316L, hematologic